Mathematical literacy in university professionals: impossibility or urgent re-significance - Rodríguez, Milagros (Revista Innova Educación, 2020)
This article studies mathematical literacy in university professionals as an impossibility or urgent re-significance from the voices of different professionals. In the investigation, interviews were conducted with nine (9) professionals from different areas. Through a qualitative inquiry, an exploratory study, thereby becoming emergent categories. The results reveal the analysis of the emerging categories surveys such as: democratization of mathematics; intellectual laziness in professionals; bad educational policies in Venezuela; false beliefs, negative emotions towards mathematics and imposition of a reductionist mathematics in the classroom and the meeting of the scientific knowledge of mathematics and the underground knowledge of it. In conclusion, mathematical literacy currently has in the professional exit lines such as: the professional promoter of mathematics as a legacy science of humanity, as the citizen responsibility of each one; minimization in communities of learning of the false beliefs of mathematics and its learning, we can all; the democratization of mathematics and re-signified educational policies in favor of the promotion of the legacy science of humanity. It encourages us to think that the problem and then the need today more than ever for mathematical literacy is everyone's responsibility.
Keywords: mathematical; literacy; re-signifying; university; professionals